공공자전거 이용수요 분석에서의 분석단위 탐구 - 황선아 (The Graduate School, Ajou University, 2024)
서울특별시의 공공자전거 이용수요는 서비스 시작 이래 매년 꾸준히 증가하 고 있는 추세이며, 2023년 하반기 시내버스 요금 인상에 따라 그 이용률은 더 증가할 것으로 예상된다. 이에 따라 추후 공공자전거 서비스의 질적 향상을 위 해 이용수요 영향요인 분석은 상당히 중요하며, 국내에서도 서울특별시, 대전광 역시, 수원특례시 등 각지에서 활발히 진행되고 있다. 그러나, 자전거가 단거리 통행 특성을 가진다는 점에도 불구하고 대부분의 연구는 읍면동 등 넓은 분석 단위를 기준으로 분석이 진행되고 있으며, 이는 결과의 신뢰도가 낮아지는 결 과를 초래할 수 있을 것으로 예상되며, 이는 가변적 공간단위 문제 즉 MAUP 문제와 연결된다. 이에 따라 본 연구에서는 공공자전거 이용수요 분석 시 적정 분석단위를 채 택하기 위해 행정동 단위, 1km 격자셀 단위, 500m 격자셀 단위, 100m 격자셀 단위 4개의 분석단위에 대해 Moran’s I 및 공간회귀분석을 수행하였다. 이 때, 공간회귀분석 시 종속변수는 공공자전거 이용건수, 독립변수는 자전거도로 연 장으로 선정하였다. Moran’s I 분석을 통하여 500m 격자셀 단위에서 공공자전거 이용건수 및 자 전거도로 연장의 공간적 상관성을 일정 수준 설명할 수 있음을 확인하였으며, 공간회귀분석을 통해 분석단위가 상이함에 따라 파라미터의 계수가 변화함을 확인하였다. 마지막으로 공간단위 분석 시 적정단위 분석 채택을 위해 공공자전거 및 PM 이 용특성을 연구한 타 연구결과를 종합한 결과 개인형 이동장치 분석 시 500m~1km 분석단위를 적정 분석단위로 채택하였으며, 본 연구에서 사용한 분석방법론을 적용하여 향후 타 교통수단(ex. 대중교통, 승용차, 도보) 분석에도 적용할 수 있을 것으로 기대된다. 주제어: MAUP, 공공자전거, 분석단위, 격자셀|The demand for using public bicycles in Seoul has been steadily increasing every year since the start of the service, and the utilization rate is expected to increase further as city bus fares increasein the second half of 2023. Accordingly, it is very important to analyze the factors influencing the demand for use to improve the quality of public bicycle services in the future, and it is being actively conducted in various places such as Seoul, Daejeon, and Suwon. However, despite the fact that bicycles have short-distance traffic characteristics, most studies are being analyzed besed on large analysis units suca as Eup, Myeon, Dong, and this is expected to result in lower reliability of the results, which is linked to the variable space unit problem, that is, the MAUP problem._x000D_ Accordingly, in this study, Moran’s I and spatial regression anaylsis were performed on four analysis units : administarative unit, 1km grid cell unit, 500m grid cell unit, and 100m grid cell unit in order to adopt appropriate analysis units when analyzing the demand for using public bicycles. At this time, in the spatial regression analysis, the dependent variable was the number of public bicycles used, and the independent variable was selected as the extension of the bicycle road._x000D_ Through Moran’s I analysis, it was confirmed that the spatial corerelation between the number of public bicycle uses and the extension of the bicycle road could be explained to a certain level in 500m grid cell units, and through spatial regression analysis, the coefficient of the parameter changed as the analysis units differed._x000D_ Finally, as a result of synthesizing the result of other studies that studied the characteristics of public bicycles and PM use to adopt appropriate unit analysis in spatial unit analysis, 500m to 1km analysis units were adopted as appropriate analysis units when analyzing individual mobile devices. The analysis methodology used in this study is expected to be applied to other transportation methos(ex. public transportation, cars, walking) analysis in the future._x000D_ Keywords: MAUP, Public Bicycle, Analysis Unit, Grid Cell
학위논문(석사)--교통공학과,2024. 2
Keywords: MAUP; 격자셀; 공공자전거; 분석단위